Signals for identifying cows at risk of subacute ruminal acidosis in dairy veterinary practice. Issue 2 (8th December 2017) - Humer, E.; Aschenbach, J. R.; Neubauer, V.; Kröger, I.; Khiaosa‐ard, R.; Baumgartner, W.; Zebeli, Q.
Summary: Controlling rumen disorders is critical to ensure successful dairy herd health management. Lactation diets of dairy cows are commonly rich in concentrates and low in physically effective fibre. Feeding of these diets increases the risk of rumen disorders with far‐reaching consequences for cattle health, welfare and sustainability of dairy production. The term subacute ruminal acidosis or SARA is often used as a synonym for poor rumen health. Being subclinical, SARA lacks of clear symptoms and is therefore difficult to diagnose and to control in the practice. This review article summarises common and identifies new direct and indirect cow signals related to SARA. We have performed a scientific evaluation and interpretation of each of these cow signals by highlighting their advantages and disadvantages from the practitioner's point of view. The gold standard of SARA cow signals still remains direct measurement of ruminal pH. However, continuous pH monitoring is cost‐intensive and often biased by sensor drift. Single‐point ruminal pH measurements by oral stomach tubing or rumenocentesis have strong limitations. Therefore, there is a need for reliable and robust markers of SARA that are easily accessible and inexpensive. Such indirect parameters are the observation of chewing and feeding activities, as well as the monitoring of milk, faecal, urine and blood variables. Also, novel technologies that allow rapid and non‐invasive measurement of the rumen mucosa thickness and ruminal motility patterns might provide advantages in SARA diagnosis. Due to several constraints of these indirect diagnostic tools, such as limited specificity and sensitivity, we strongly recommend using a combination of the signals to reliably identify cows at risk of SARA in a dairy herd.